Persepsi masyarakat terhadap rencana pembangunan pembangkit listrik tenaga panas bumi (PLTP) di Desa Idamdehe, Kabupaten Halmahera Barat, Provinsi Maluku Utara - Djumaty, Brian L; Hayam Dey, Nina Putri (Penerbit STKIP PGRI Bangkalan, 2018)
Development is a process to accelerate economic growth, reduce gaps and eradicate poverty. Besides that development is also a multidimensional process of important changes in social structure, attitude of the people and national institutions. Therefore, in this study the authors will examine the public perception of the planned development of Geothermal Power Plant (PLTP) in Idamdehe Village, District Jailolo, West Halmahera, North Maluku Province.  The reason the author took this topic because in the village will be built PLTP. The research methodology used is qualitative descriptive. From the results of research shows that the development plan of PTLP in Idamdehe village has been socialized since 2011-2013. From the results of socialization of the community get information about PTLP. There are three groups of perceptions about the PLTP development plan that is Agree, Disagree and Doubtful.